Epidemiological, Clinical Profiles and Outcome of Bronchiolitis in Iraqi Children - Al-Janabi, Muhi K.; Nadhem, Haider; Aziz, Nadia (Journal of the Faculty of Medicine Baghdad, 2008)
Background:Bronchiolitis is the first episode of wheezing associated with low-grade fever, rhinitis, tachypnea, and increase respiratory effort in a previously healthy infant during the wintermonths. It is the most common disease of the lower respiratory tract.Methods:This is a case control study carried out on one hundred infants with a mean age of 3.9 months ± 2.2 months admitted to Children Welfare Teaching Hospital in Medical City –Baghdad with acute bronchiolitis during the period from 1st January 2006 to 1st April 2006. epidemiological risk factors, clinical presentations, chest X-ray findings, treatment,complications and outcome were analyzed. Another one hundred infants (age and sex matched) were seen in the outpatient clinical in the same period and for health problemsother than bronchiolitis were taken as a control group. Chi square test was used and a P 30 with bronchiolitis. Fever >38.1C was significantlymore common in infants with bronchiolitis > 6 months of age than those less than 6 months.Conclusions:The mean clinical scores of severity, the mean duration of hospitalization and Chest Xray findings were higher in: male sex, age